PERLAKUAN PEMERINTAH MYANMAR TERHADAP MINORITAS MUSLIM ROHINGYA PERSEPKTIF SEJARAH DAN HUKUM INTERNASIONAL - Veronika Wulandari (Universitas Pendidikan Ganesha, 2022)
According to some Myanmar historians, the word Rohingya recently became popular in the 1920s, after Myanmar's independence. Genocide didn't exist before 1944. This is a very specific term, referring to violent crimes committed against a group for the purpose of destruction. Human rights (HAM), as outlined in the 1944 UN universal declaration of human rights, a Polish Jewish advocate named Raphael Lemnkin (1900-1959) attempted to describe the Nazi policy of systematic massacres, including the extermination of European Jews. The purpose of this study is to identify differences in legal systems dealing with legal disciplines. Rohingya conflict cannot be separated from Myanmar politics itself. Changes in leadership affect the position of the Rohingya in Myanmar. The Rohingya were once recognized by the Myanmar government when Prime Minister U Nu was in power, this was evidenced by their representation in the Myanmar parliament. The end of U Nu's reign and being replaced by the Military Junta Rezin resulted in the Rohingya not being recognized in the Myanmar constitution. Punishment of violations by the state requires a variety of international and regional human rights law instruments have developed severe human rights. Even customary international law strictly prohibits any kind of punishment for flagrant and persistent violations of human rights. The Indonesian government's proposal to use several diplomatic channels of the OIC, ASEAN, and the UN Security Council is a substitute for the Indonesian nation to be prominent in the IKO area and ASEAN has already taken part in diplomatic relations. On the one hand, Indonesia is a country with a Muslim majority in the universe. Based on humanitarian intentions and universal principles the protection of the Rohingya minority is very important. On the basis of race, religion, and other factors, Indonesia has repeatedly condemned all types of discrimination.